Expression of tyrosinase, MIA and MART-1 in sentinel lymph nodes of patients with malignant melanoma - Hochberg, M.; Lotem, M.; Gimon, Z.; Shiloni, E.; Enk, C.D. (British journal of dermatology (1951), 2002)
Summary Background Regional lymph node status is an important predictor of survival in patients with malignant melanoma. Mapping of sentinel lymph nodes using sensitive molecular techniques has recently been introduced. Malignant melanoma is heterogeneous in terms of its biological, immunological and metastatic properties, and melanoma cells exhibit a polymorphous expression of tumour markers. Thus, assays that include multiple markers appear to be more sensitive than single‐marker assays. Objectives To characterize the molecular profiles of melanoma cells in sentinel lymph nodes employing the mRNA expression of tyrosinase, MIA and MART‐1 as markers. Methods Samples of sentinel lymph nodes from 17 melanoma patients and 18 control nodes from non‐melanoma patients were assayed by reverse transcriptase–polymerase chain reaction, using specific primers for each marker. Results We found that both tyrosinase and MIA expression were sensitive indicators of micrometastases in sentinel lymph nodes that were negative on routine histopathological examination, and that the finding of micrometastases expressing MART‐1 in sentinel lymph nodes was negatively correlated with overall survival. Conclusions Characterization of the molecular profiles of melanoma cells constitutes a valid means of detecting metastatic melanoma cells in sentinel lymph nodes, and of predicting the survival of melanoma patients.